Composition, production rate and characterization of Greek dental solid waste. (May 2018) - Mandalidis, Alexandros; Topalidis, Antonios; Voudrias, Evangelos A.; Iosifidis, Nikolaos
Highlights: We studied dental solid waste (DSW) production by 20 dental practices in Greece. Hazardous waste fraction comprised 92% and domestic-type waste 8% w/w of total DSW. Hazardous waste unit production rate was 48.7 ± 1.3 g/patient/d (mean ± standard error). Unit production rates for DSW were 53.3 ± 1.4 g/patient/d and 381 ± 15 g/practice/d. Bulk density, calorific value, moisture, ash and volatile solids were measured. Abstract: The overall objective of this work is to determine the composition, characterization and production rate of Greek dental solid waste (DSW). This information is important to design and cost management systems for DSW, for safety and health considerations and for assessing environmental impact. A total of 141 kg of DSW produced by a total of 2542 patients in 20 dental practices from Xanthi, Greece was collected, manually separated and weighed over a period of four working weeks. The waste was separated in 19 sub fractions, which were classified in 2 major categories, according to Greek regulations: Domestic-type waste comprising 8% and hazardous waste comprising 92% by weight of total DSW. The latter was further classified in infectious waste, toxic waste and mixed type waste (infectious and toxic together), accounting for 88.5%, 3.5% and 0.03% of total DSW by weight, respectively. The overall unit production rates (mean ± standard error of the mean) were 381 ± 15 g/practice/d and 53.3 ± 1.4 g/patient/d for total DSW, 337 ± 14 g/practice/d and 46.6 ± 1.2 g/patient/d for total infectious DSW, 13.4 ± 0.7 g/practice/d and 2.1 ± 0.1 g/patient/d for total toxic DSW and 30.4 ± 2.5 g/practice/d and 4.6 ± 0.4 g/patient/d for domestic-type waste. Daily DSW production was correlated with daily number of patients and regression correlations were produced. DSW was subject to laboratory characterization in terms of bulk density, calorific value, moisture, ash and volatile solids content. Measured calorific values were compared to predictions from empirical models.